Background of Malaysian private institutions of higher learning and challenges faced by academics - Arokiasamy, Lawrence; Ismail, Maimunah; Ahmad, Aminah; Othman, Jamaliah (The Journal of International Social Research, 2009)
Private institutions of higher learning (IHLs) are as important as the public ones in preparing Malaysia as an educational hub in the Asian region. This article discusses background of Malaysian private institutions of higher learning and career challenges faced by the academics. The background consists of their account of establishment to the current development. The challenges include uncertain career path of academics, problems of tasks in teaching versus research due to lack of funding, opportunities for sabbatical leave and pursuance of higher education as well as participation in conferences abroad. Thus understanding challenges is important for the academics in private IHLs to prepare, plan and develop their careers.